Sustentabilidade dos sistemas agrícolas: uma análise no contexto da agrodiversidade. Um estudo de caso na Amazônia Oriental - CAHETÉ, Frederico Luiz Silva (2005)
The study has as objective to evaluate the process of sustainability e in agricultural systems, having as parameter the energetic and economic flows amongst its compartments, whose dynamic is regulated for the agro diversity of an agrarian environment in transition. The field work was carried through in the municipality of Igarap?-A?u, Northeast of the Par? State. Initially was made one survey in 60 productive units, following itself of application of a questionnaire in 25 units, systemic modeling in 11, and interviewing with on local agents productive, which them are direct or indirectly the branches of agricultural interests. Analyze of the data involved a modeling, subsidized for one exam of context. The result of analyses disclosed mechanisms that characterize the distinct logicals that guide the agro ecologic and economic processes. The model bred allows: to configure the dynamical structural of these systems, to estimate theirs respective levels of dependence to the resources, as well as the necessary time and area to obtain of equivalents costs of chance to the processes of agricultural production, to identify limiting points of agrarian evolution in the Municipality. These ecological/economics parameters, pioneering defined, can be considered as basic tool for planning a sustainable agrarian development.